Information Literacy – Curriculum Integration with Medical School’s Syllabus - Haraldstad, Anne-Marie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The medical students are the researchers and clinicians of the future, and becoming information literate is of utmost importance. In our library medical students is a user group of high priority, and in the following I will present the information literacy programme developed for this group, and some future plans.